PROSES KONSELING DALAM MEMBANTU MENGATASI PERMASALAHAN SANTRI DI PONDOK PESANTREN - Alzada Ratu Naila Fauziah; Putri Khairunnisa; Muhammad Azhar Arrabani; Agus Sukirno (STKIP Subang, 2026)
Research on the counseling process in Islamic boarding schools (pesantren) reveals that a guidance and counseling program is essential for the development of students. Therefore, a policy is needed to support the guidance and counseling program. Using written data sources such as journals and articles, this study aims to understand the guidance and counseling process in Islamic boarding schools. The results indicate that the guidance and counseling process differs from that in formal educational institutions, stemming from Islamic values ​​and teachings. Because Islamic boarding schools often conduct Islamic activities or curricula, guidance and counseling must be integrated into Islamic boarding school activities.